2014
DOI: 10.4028/www.scientific.net/ast.94.97
|View full text |Cite
|
Sign up to set email alerts
|

A New Matrix for Conditioning Chloride Salt Wastes from the Electrorefining of Spent Nuclear Fuel

Abstract: A novel method proposed by Korea Atomic Energy Research Institute has been applied to the treatment of chloride salt wastes coming from electrorefining of spent nuclear fuel, which allows to separate uranium from fission products. It is based on a matrix, SAP (SiO2-Al2O3-P2O5), synthesized by a conventional sol-gel process, able to stabilize the volatile salt wastes due to the formation of metalaluminosilicates, metalaluminophosphates and metalphosphates. With this method a higher disposal efficiency and a low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 6 publications
3
7
0
Order By: Relevance
“…Sodalite is a natural aluminosilicate containing iodine/chlorine, hydroxide, and other anions in its composition and is a well-known efficient feldspathoidal mineral for the immobilization of chloride- and iodide-containing wastes (Figure B). , Various synthesis conditions were optimized for the development of sodalite-based matrices, e.g., the application of sodium aluminate and silica precursors using kaolinite, nepheline, or zeolite A (LTA). In South Korea, the Korea Atomic Energy Research Institute (KAERI) also developed SAP as an efficient immobilization matrix for chloride-containing wastes. , The authors proposed that the SAP can be synthesized by the sol–gel method, and it is highly capable of capturing and stabilizing volatile salt wastes in the form of metal aluminosilicates, aluminophosphates, and phosphates . Moreover, the design and synthesis of glassy waste form (U-SAP) was developed as an alternative matrix for other SAP waste forms …”
Section: Types Of Waste Formsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sodalite is a natural aluminosilicate containing iodine/chlorine, hydroxide, and other anions in its composition and is a well-known efficient feldspathoidal mineral for the immobilization of chloride- and iodide-containing wastes (Figure B). , Various synthesis conditions were optimized for the development of sodalite-based matrices, e.g., the application of sodium aluminate and silica precursors using kaolinite, nepheline, or zeolite A (LTA). In South Korea, the Korea Atomic Energy Research Institute (KAERI) also developed SAP as an efficient immobilization matrix for chloride-containing wastes. , The authors proposed that the SAP can be synthesized by the sol–gel method, and it is highly capable of capturing and stabilizing volatile salt wastes in the form of metal aluminosilicates, aluminophosphates, and phosphates . Moreover, the design and synthesis of glassy waste form (U-SAP) was developed as an alternative matrix for other SAP waste forms …”
Section: Types Of Waste Formsmentioning
confidence: 99%
“…225,226 The authors proposed that the SAP can be synthesized by the sol−gel method, and it is highly capable of capturing and stabilizing volatile salt wastes in the form of metal aluminosilicates, aluminophosphates, and phosphates. 227 Moreover, the design and synthesis of glassy waste form (U-SAP) was developed as an alternative matrix for other SAP waste forms. 228 de Angelis et al reported a detailed experimental investigation of sodalite and SAP matrices (consisting of silica (SiO 2 ), alumina (Al 2 O 3 ), and phosphorus pentoxide (P 2 O 5 )) as potential candidate for the confinement and immobilization of spent chloride salt waste.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…The Korea Atomic Energy Research Institute (KAERI) proposed an immobilization matrix for chloride salt wastes, termed SAP, consisting of SiO 2 ,Al 2 O 3 and P 2 O 5 [27,28]. This matrix, synthesized by a conventional sol-gel process, is able to stabilize volatile salt wastes due to the formation of metal aluminosilicates, aluminophosphates and phosphates, generating chlorine gas [29]. Glass can be added to the SAP matrix as a chemical binder giving rise to higher disposal efficiency and to a lower volume of waste compared with other immobilization matrices [27,30].…”
Section: Introductionmentioning
confidence: 99%
“…This matrix, synthesized by a conventional sol-gel process, is able to stabilize volatile salt wastes due to the formation of metal aluminosilicates, aluminophosphates and phosphates, generating chlorine gas [29]. Glass can be added to the SAP matrix as a chemical binder giving rise to higher disposal efficiency and to a lower volume of waste compared with other immobilization matrices [27,30]. A recent evolution of SAP, the glassy wasteform U-SAP, shows even better performances with respect to other SAP wasteforms [31,32].…”
Section: Introductionmentioning
confidence: 99%